THE USE OF STUDENT TALK TECHNIQUE IN TEACHING SPEAKING TO THE ADVANCE STUDENT OF ESADA 2020 - Dian Kurniasih Wahyusari; M Rifqi Zainul Azka (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2020)
This study is to find out the result of â€œ The Use Of Student Talk in teaching speaking To The Advance Student Of Esada Course Darussalam 2020 â€. The subject of the research is the student of advance class 2020 that consists of 13 students. The researcher just focuses on the six students that have low speaking skill. These students are chosen based on their speaking skill score before the reseacher observes the class. The reseacher took score from the teacher assesment of the speaking final test. The research design used in this study is a classroom action research.and researcher use mix method to anaylisis data. The result of analysis shows that the implementation of the student talk technique increases those aspects. Based on the finding, the improvement of simple T-Test was conducted T value ( 6000 ) > T table ( 2,776 ). This shows that there are significant that the use of student talk was effected on advance student. The researcher recommends this student talk technique, because it is really useful to improve the student speaking skill.